2009
DOI: 10.1111/j.1567-1364.2009.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose promotes the survival ofSaccharomyces cerevisiaeduring lethal ethanol stress, but does not influence growth under sublethal ethanol stress

Abstract: Trehalose is known to protect cells from various environmental assaults; however, its role in the ethanol tolerance of Saccharomyces cerevisiae remains controversial. Many previous studies report correlations between trehalose levels and ethanol tolerance across a variety of strains, yet variations in genetic background make it difficult to separate the impact of trehalose from other stress response factors. In the current study, investigations were conducted on the ethanol tolerance of S. cerevisiae BY4742 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 48 publications
1
41
0
1
Order By: Relevance
“…Furthermore, both the hybrid and diploid of IB1304 cells showed increased tolerance of stress induced by ethanol, freezing and heat shock although the hybrid did not acquire tolerance of H 2 O 2 stress (Table 7). Consistent with our results are observations that high levels of intracellular trehalose conferred tolerance of freezing for commercial baker s yeast (Shima et al, 1999), and improved the resilience of cells when these were incubated in the presence of lethal 10 to 18% (v/v) ethanol concentrations (Bandara et al, 2009), and that trehalose can function as a positive regulator of the transcriptional response to heat shock (Conlin and Nelson, 2007). Its tolerance of a wide range of stresses makes this strain highly useful for applications where these adverse environmental conditions have to be countered and for the study of the molecular mechanisms at play in response to these stresses.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, both the hybrid and diploid of IB1304 cells showed increased tolerance of stress induced by ethanol, freezing and heat shock although the hybrid did not acquire tolerance of H 2 O 2 stress (Table 7). Consistent with our results are observations that high levels of intracellular trehalose conferred tolerance of freezing for commercial baker s yeast (Shima et al, 1999), and improved the resilience of cells when these were incubated in the presence of lethal 10 to 18% (v/v) ethanol concentrations (Bandara et al, 2009), and that trehalose can function as a positive regulator of the transcriptional response to heat shock (Conlin and Nelson, 2007). Its tolerance of a wide range of stresses makes this strain highly useful for applications where these adverse environmental conditions have to be countered and for the study of the molecular mechanisms at play in response to these stresses.…”
Section: Discussionsupporting
confidence: 80%
“…[12][13][14][15] Trehalose, a non-reducing disaccharide, works as an energy source in yeasts, bacteria, fungi, invertebrates, insects and plants. 16,17 Many research demonstrated that the higher trehalose accumulated in the yeast cell the higher tolerance against various environmental stresses, for instance ethanol stress, 18 heat stress, 19 saline stress, 20 and various other environmental stresses. 21,22 In S. cerevisiae, concentration of trehalose is regulated by synthesis enzymes and hydrolysis enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PGM1 and PGM2 double null mutants accumulated lower levels of trehalose in S. cerevisiae than wild type (Boles et al, 1994). Trehalose is known for its important role in protecting cell membrane against harsh environment stresses ( Sharma, 1997;Bandara et al, 2009), therefore, the up-regulation of PGM1 suggests that it may be considered as multiple stress-tolerance related gene. GAL10 encodes a bifunctional enzyme with mutarotase and UDP galactose 4-epimerase activities (Majumdar et al, 2004).…”
Section: Glycolysis/gluconeogenesismentioning
confidence: 99%
“…The protective role of trehalose is an obvious interpretation of its production in response to stress. It is well known that trehalose accumulates in yeast cells under nutrient starvation, heat stress and ethanol stress (Parrou et al, 1999;Sharma, 1997;Bandara et al, 2009). However, trehalose metabolism genes, except PGM1, were mostly neither induced nor repressed at the end of VHG fermentation.…”
Section: Genes Involved In Heat Shock Protein (Hsp)mentioning
confidence: 99%